La letteratura si salverà dall’estinzione? Sulla sopravvivenza dei libri e delle storie in una prospettiva ecodistopica (ENTHYMEMA, 2023)
The article focuses, from a perspective that makes use of the terminological and theoretical toolkit of media ecology, on some fictional texts – Douglas Coupland’s Generation A and Steven Hall’s The Raw Shark Texts – in which the theme of the possible extinction or survival of literature is dealt with in a reading key that we could define as ecodystopian. At a time of climate change and environmental disasters, these texts express deep concerns about the digitally altered narrative environment by drawing heavily on the metaphorical field of sustainability, exploitation and depletion of resources, and evolution and regeneration of forms, with a particular focus on the aquatic element.
Keywords: Douglas Coupland; Steven Hall; Distopia; Media Ecology; Narrative Ecosystems